MRT Letter: A Novel Tegumental Gland in Female Imagoes of the Neotropical Termite Cornitermes cumulans (Isoptera, Termitidae, Syntermitinae) - Costa-Leonardo, Ana Maria [UNESP]; Haifig, Ives [UNESP] (Wiley-liss, 2010)
In general, the exocrine glands of social insects are structures involved in the chemical communication associated with social life. Here, we report the discovery of an unknown tegumental gland that is present in the female imagoes of Cornitermes cumulans and occurs next to the well-developed tergal glands that have previously been described. The tegumental glands release their secretion in the intersegmental membrane and are composed of bicellular units, a secretory cell and a canal cell, that are closely located to the epidermal cells in the inferior part of the eighth and ninth tergites. The ultrastructure of the glandular cells showed abundant smooth endoplasmic reticulum, suggesting that the secretion may be pheromonal, although its function is still unknown. These exocrine structures are facing the tergal glands, and we hypothesized that they act synergistically with the tergal glands to generate short-range attraction during tandem behavior. Microsc. Res. Tech. 73: 1005-1008, 2010. (C) 2010 Wiley-Liss, Inc.
Keywords: exocrine gland; class 3 cells; canal cells; ultrastructure; Isoptera